HUBUNGAN FAKTOR INTERNAL DAN EKSTERNAL DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS TELADAN KECAMATAN MEDAN KOTA - Dwi Damayanti; Jemadi .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Anemia in pregnancy will increase the risk of hemorrhage which is the prominent cause of maternal mortality in Indonesia. Based on RISKESDAS 2013, prevalence of anemia in pregnancy in Indonesia is 37,1%. Maternal mortality is the indicator of maternal health care and also the evaluator of public health condition within the region. Therefore, the aim of this study is to find out the risk factors of anemia in pregnancy to maximize the effort in reducing maternal mortality. This is Cross Sectional study conducted on January-October 2017. Sample is 3rd trimester pregnant women in the Region of Teladan Public Health Center with 108 samples chosen by Purposive Sampling. Data collected by interviewed based on prepared questioner and measured hemoglobin level using electronic device EasyTouch GCHb. Bivariat analysis using Chi-square test and Fisher Exact test and Multivariat analysis using Logistic Regression. The result shows that anemia in 3rd trimester pregnancy is 64,8%. Statistic analysis at significant level α=0,05 shows there are correlation between nutritional status (p=0,010) and intake of iron supplementation (p=0,000) with anemia in pregnancy. Meanwhile age (p=1,000), parity (p=0,719), birth spacing (p=0,485), education (p=0,110), and frequency of antenatal (p=0,148) have no correlation with anemia in pregnancy. Multivariate analysis shows that the most dominant factor of anemia in pregnancy is intake of iron suplementation (Exp(B)=8,107). Pregnant women are advised to fulfill the needs of iron and nutrition during pregnancy. As for the public health center, it is important for antenatal care to be conducted in Maternal and Child Health Center in order to reach the pregnant women who are not mobile to visit the public health center. Keyword: Anemia, 3rd Trimester Pregnancy, Teladan Public Health Center